2000
DOI: 10.1016/s0006-3495(00)76609-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of a Crystalline Insulin Analog Complex with Protamine by Atomic Force Microscopy

Abstract: Crystallographic studies of insulin-protamine complexes, such as neutral protamine Hagedorn (NPH) insulin, have been hampered by high crystal solvent content, small crystal dimensions, and extensive disorder in the protamine molecules. We report herein in situ tapping mode atomic force microscopy (TMAFM) studies of crystalline neutral protamine Lys(B28)Pro(B29) (NPL), a complex of Lys(B28)Pro(B29) insulin, in which the C-terminal prolyl and lysyl residues of human insulin are inverted, and protamine that is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…The NPH-like crystals of insulin lispro are also oblong tetragonal crystals, similar to those observed with NPH insulin formulations [56]. The NPH-like suspension of insulin lispro possesses the physicochemical properties relative to human insulin NPH [60]; however, to prepare the NPHanalogous tetragonal crystals with intermediate-acting time-action, significant modifications to the protamine/insulin crystallization procedure was required due to the reduced self-association properties of insulin lispro [61].…”
Section: Long-acting Insulin Analog Formulations (Basal Insulin)supporting
confidence: 52%
“…The NPH-like crystals of insulin lispro are also oblong tetragonal crystals, similar to those observed with NPH insulin formulations [56]. The NPH-like suspension of insulin lispro possesses the physicochemical properties relative to human insulin NPH [60]; however, to prepare the NPHanalogous tetragonal crystals with intermediate-acting time-action, significant modifications to the protamine/insulin crystallization procedure was required due to the reduced self-association properties of insulin lispro [61].…”
Section: Long-acting Insulin Analog Formulations (Basal Insulin)supporting
confidence: 52%
“…5E and 5F. The height mode of AFM reflects the surface property of the object, while the phase mode measures the stiffness or elasticity difference of the object [32]. For β-carotene/copolymer particles, the height image shows globular shape with smooth surface.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the unique combination of GISAXS and micrometer sized beam, our investigation of lysozymes confirms the higher performance of the nanotemplate method in producing crystals and provides new insights on the differential early steps of crystal nucleation and growth within the drop for both the lysosymes and the cytochromes. µGISAXS data allow indeed monitoring crystal formation at a resolution and a scale previously unmatchable even with respect to what has been significantly achieved by AFM studies [Li et al, 1999; Yip et al, 2000; McPherson et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…This technique can be used to measure the growth unit sizes on protein crystal faces as well, allowing their molecular growth mechanisms to be determined experimentally. It was applied to probe the growth mechanism of the (110) face of tetragonal lysozyme crystals [Li et al, 1999]; in this study the latest step of crystal growth is observed, often on the large crystal terrace [Yip et al, 2000].…”
mentioning
confidence: 99%